2014
DOI: 10.1177/0040517514545257
|View full text |Cite
|
Sign up to set email alerts
|

Research into the specifications of woven composites obtained from raffia fibers pretreated using the ecological method

Abstract: Studies on using cellulosic natural fibers as reinforcement for composites are rapidly growing. The aim of this study is using a raffia-based woven fabric as reinforcement for composites that are grown in the Mediterranean Zone of Turkey. These fabrics benefit from their mechanical performances, low density and their biodegradability. However, it is necessary for the fabrics to form adhesion in the matrix. Therefore, chemical processes should be applied onto the surface of the raffia-based woven fabrics. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…The microwave energy method was more rapid, uniform and efficient than other two methods. In our previous study, we have observed that laccase enzyme has quickly affected the fiber structure of raffia-based fabric in a shorter time with the microwave energy method [28].…”
Section: The Results Of Elongation Propertiesmentioning
confidence: 99%
“…The microwave energy method was more rapid, uniform and efficient than other two methods. In our previous study, we have observed that laccase enzyme has quickly affected the fiber structure of raffia-based fabric in a shorter time with the microwave energy method [28].…”
Section: The Results Of Elongation Propertiesmentioning
confidence: 99%
“…The fibers were shaken under running water until cleaned and they were dried in an oven 70 ° C for 6 h. After drying, they were conditioned 48 h prior to testing under ±20°C and 65 ± 2 RH% condition as suggested in literature. 36–38
Figure 1.Appearance of conditioned fibers of (a) cotton (b) artichoke (c) luffa (d) banana.
…”
Section: Methodsmentioning
confidence: 99%
“…The fibers were shaken under running water until cleaned and they were dried in an oven 70 °C for 6 h. After drying, they were conditioned 48 h prior to testing under ±20°C and 65 ± 2 RH% condition as suggested in literature. [36][37][38] LF is a tropical creeping annual plant and it grows well in the areas of the Mediterranean climate, in Turkey. The lengths of fiber were between 400 mm and 600 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Varieties of properties of several textile materials at different levels have been changed through microwaving. Microwave treatments have been used for changing properties, such as coloring [10], fiber-surface roughness [11], and hydrophilicity [12]. Microwaving has also been used to extract fibers [13] and polysaccharides from algae [14] and to graft polymer on flax fibers [15].…”
Section: Introductionmentioning
confidence: 99%